2015
DOI: 10.3390/en8077261
|View full text |Cite
|
Sign up to set email alerts
|

Energy Performance Database of Building Heritage in the Region of Umbria, Central Italy

Abstract: Abstract:Household energy consumption has been increasing in the last decades; the residential sector is responsible for about 40% of the total final energy use in Europe. Energy efficiency measures can both reduce energy needs of buildings and energy-related CO2 emissions. For this reason, in recent years, the European Union has been making efforts to enhance energy saving in buildings by introducing various policies and strategies; in this context, a common methodology was developed to assess and to certify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…In a regional study of a residential building stock in Umbria, Italy, energy performance certificates were used in order to understand the potential for energy and CO 2 savings in different age segments. The heritage building as a concept was used for defining the older segments of the building stock [17]. In order to develop a methodology for residential urban building stocks, different building-specific data were used as inputs to identify trends and tendencies in energy performance in a selected building stock in the city of Gothenburg [18].…”
Section: Energy Efficiency In Historic Building Stocksmentioning
confidence: 99%
“…In a regional study of a residential building stock in Umbria, Italy, energy performance certificates were used in order to understand the potential for energy and CO 2 savings in different age segments. The heritage building as a concept was used for defining the older segments of the building stock [17]. In order to develop a methodology for residential urban building stocks, different building-specific data were used as inputs to identify trends and tendencies in energy performance in a selected building stock in the city of Gothenburg [18].…”
Section: Energy Efficiency In Historic Building Stocksmentioning
confidence: 99%
“…In a regional study of building stock of residential buildings in Umbria, Italy, energy certificates were used to determine the potential of energy and CO 2 savings in different age segments of the building stock. In this case, the concept 'heritage buildings' was used to define the older segments of the building stock (Buratti et al, 2015). To develop a methodology for residential urban building stocks, building data were used as input to reveal trends in energy performance in a selected building stock in Gothenburg, Sweden.…”
Section: Energy Efficiency In Historic Building Stocksmentioning
confidence: 99%
“…Buratti et al [25] analysed the state of the art of energy certification of households in an Italian region and compared results with national and international indicators, making it possible to evaluate actual energy performances and savings. Focusing on the age of buildings, the results showed that just 6.0% of buildings built before 1950 are provided an energy certificate, and this building stock has the highest energy consumption.…”
Section: Energy Efficiency In Historical Buildings: Some Experiencesmentioning
confidence: 99%